A priority-driven, policy-relevant research program to support a response to blood-borne viruses and sexually transmissible infections in NSW, Australia - Tina Gordon; Cherie Power; Tim Duck; Heather-Marie A Schmidt; Joanne Holden (Sax Institute, 2018)
Objectives: Strong collaboration between researchers, policy makers and practitioners supports the use of research evidence in policy and practice. Strategies for increasing the use of evidence in policy development and implementation include creating more opportunities for closer collaboration between researchers and policy makers, ensuring research syntheses are more accessible to policy makers, and increasing workforce capacity to utilise evidence. Type of program or service: The BBV & STI Research, Intervention and Strategic Evaluation Program, 2014-2019 (BRISE) is a coherent and integrated program that delivers policy-relevant research, strategic advice, capacity building and communications to support the response to blood-borne viruses (BBV) and sexually transmissible infections (STI) in New South Wales (NSW), Australia. BRISE has five key objectives: generate high-quality research; maximise the use of research; build research capacity; communication and marketing; and governance and management. Results: BRISE facilitates the coproduction of research where researchers and policy makers are meaningfully involved in all stages of research priority setting and codesign from development to application, building an understanding of the way evidence is generated to allow for greater integration between research and use of evidence. Lessons learnt: Bringing multiple research projects together under a single contract and budget provided the NSW Ministry of Health (the Ministry) with cost efficiencies and streamlined contract management and project reporting. A flexible work plan allowed for a mix of longer-term (up to 5-year) projects and shorter projects that were responsive to emerging policy-relevant research priorities. The Ministry became involved in the production of collaborative research as a research partner, rather than solely a research 'funder'. The joint management of research projects involving a policy officer from the Ministry provided opportunities for individuals to build on their research capabilities and literacy. Collaborative priority setting and project work, and increased research literacy, improved the likelihood that research generated would then be used in policy and practice.